Image Analysis of the Influence of the Multi-Mission Radioisotope Thermoelectric Generator (MMRTG) on the Mars Environmental Dynamics Analyzer at Extremely Low Reynolds Number - Ángel Antonio Rodríguez-Sevillano; María Jesús Casati-Calzada; Rafael Bardera-Mora; Juan Carlos Matías-García; Estela Barroso-Barderas; Emilio Fernández-Rivero (Applied Sciences)
This study analyzes the influence of the Multi-Mission Radioisotope Thermoelectric Generator (MMRTG) on the Mars Environmental Dynamics Analyzer (MEDA) station located on board the Perseverance rover (Mars 2020). A novel visualization methodology was developed using a hydrodynamic towing tank and 3D-printed models created through additive manufacturing. This experimental approach, not previously applied in this context, proved to be a cost-effective alternative for studying thermal interactions while providing accurate preliminary insights into the behavior of thermal plumes under Martian-like conditions. Key factors such as the extremely low Reynolds number, an increasing temperature of the model, and atmospheric properties similar to those in Mars were incorporated. The findings suggest that the MMRTG’s thermal plume may significantly influence MEDA’s performance due to the plume’s height and its interaction with the surrounding environment.